Identification and Pathogenicity Analysis of Huaxiibacter chinensis Qf-1 in Mink (Neogale vison) - Yao Chen; Haotian Cai; Xiaoyang Wu; Xibao Wang; Yongquan Shang; Qinguo Wei; Weilai Sha; Yan Qi; Shuli Liu; Honghai Zhang (Microorganisms)
Mink (Neogale vison) is a commercially farmed animal of global importance. However, disease outbreaks during farming not only cause significant economic losses but also substantially increase the risk of zoonotic infections. The identification and characterization of pathogenic bacteria remain a major bottleneck restricting the development of healthy and sustainable mink farming. In this study, an LB medium was used to isolate a pale-white, rod-shaped, Gram-negative bacterial strain, Qf-1, from minks with pneumonia. Based on morphological characteristics, biochemical properties, 16S rRNA gene sequencing, and average nucleotide identity (ANI) analysis, strain Qf-1 was identified as Huaxiibacter chinensis Qf-1. Under laboratory conditions, H. chinensis Qf-1 induced typical pneumonia symptoms in Kunming mice. Furthermore, whole-genome sequencing of H. chinensis Qf-1 revealed its genome to be 4.77 Mb and to contain a single chromosome and one plasmid. The main virulence genes of H. chinensis Qf-1 were primarily associated with flgB, flgC, flgG, aceA, hemL, tssC1, csgD, hofB, ppdD, hcpA, and vgrGA, functioning in motility, biofilm formation, colonization ability, and secretion systems. Our findings contribute to a better understanding of their pathogenic mechanisms, thereby laying a theoretical foundation for further investigation into the complex interactions between gut microbiota and the host.